Supervisi Kepala Sekolah dalam Peningkatan Profesionalisme Guru di SMA Primaganda Jombang - Ali Mustofa; Maulana Adinata (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2019)
The quality of learning is strongly influenced by the professional quality of teacher performance, therefore efforts to improve the professional abilities of teachers in carrying out the learning and teaching process can be through supervision assistance. The professionalism of teachers in Primaganda High School is still said to have not yet achieved optimal results, so through the supervision activities of the principal provides guidance, motivation and technical assistance to teachers who experience difficulties in learning activities so as to improve teacher professionalism. The results of the study indicate that that the role of the principal's supervision in increasing the professionalism of teachers in Primaganda High School has strived to achieve optimal results. Aspects of the role of supervision carried out by the principal is to do (1) coordinator, (2) consultant, (3) group leader, and (4) evaluator. The principal uses the technique of supervision with group supervision and individual supervision. Teacher professionalism at Primaganda High School is carried out with the following aspects; pedagogic aspects, personality aspects, social aspects, and professional aspects. Professionalism of teachers in Primaganda Jombang High School is quite good. The achievement of pedagogical aspects is well categorized, personality aspects are well categorized, social aspects are categorized very well, and professional aspects are sufficiently categorized.